2008
DOI: 10.1002/pssa.200824083
|View full text |Cite
|
Sign up to set email alerts
|

The characterizations of superconducting MoC/Mo2C nanocomposites embedded in a magnetic graphite matrix

Abstract: A three‐dimensional molybdenum‐carbides/graphite network formed by superconducting MoC/Mo2C nanograins embedded in a magnetic graphite matrix was fabricated. The temperature dependence of magnetization of the MoC/Mo2C nanocomposites indicates that the superconducting transition temperatures (TC) of Mo2C and MoC nanocrystals are 8 K and 11.5 K, respectively. These transition temperatures are lower than those of their corresponding bulk counterparts, due to the detrimental influence of magnetic graphite. The mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…During the sintering/melting step in the SPS process, the metallic phase forms a liquid in which dissolution and transport of the molybdenum mass takes place. The observed transformations can be explained by the possibility of spinodal decomposition of the nc-(Ti,Mo)C carbide into TiC and metastable MoC carbides [ 32 , 33 , 34 ]. Under such conditions, the reaction between titanium matrix and MoC occurred according to the equation: Ti + MoC = TiC + Mo …”
Section: Resultsmentioning
confidence: 99%
“…During the sintering/melting step in the SPS process, the metallic phase forms a liquid in which dissolution and transport of the molybdenum mass takes place. The observed transformations can be explained by the possibility of spinodal decomposition of the nc-(Ti,Mo)C carbide into TiC and metastable MoC carbides [ 32 , 33 , 34 ]. Under such conditions, the reaction between titanium matrix and MoC occurred according to the equation: Ti + MoC = TiC + Mo …”
Section: Resultsmentioning
confidence: 99%
“…37 Although it can be seen from XPS Mo 3d spectra that all the samples contained Mo 2+ carbide species on the surfaces, only the C 1s signal of M-800 showed a peak at 283.6 eV, corresponding to carbidic carbon involved in Mo-C bonds. 38 This was probably due to the fact that in the case of other samples, the carbidic carbon species were so low in concentration that their corresponding peak areas were overshadowed by those of sp 2 carbon. Subsequently, further information regarding the carbon deposit during the carburization process was obtained by Raman spectroscopy (Fig.…”
Section: Preparation and Characterization Of Mo Carbidesmentioning
confidence: 98%
“…The peak at a binding energy of 228.5 eV was assigned to Mo 3d 5/2 of Mo 2+ (carbide), [31][32][33] Table 2 that, no matter whether it was bulk or supported sample, the concentration of Mo 2+ carbide rapidly increased upon increasing the carburizing temperature from 650 to 800 1C. 38 This was probably due to the fact that in the case of other samples, the carbidic carbon species were so low in concentration that their corresponding peak areas were overshadowed by those of sp 2 carbon. These results indicated that both the increase of temperature and the replacement of RH by the PH method could promote the carburization process, which was in accordance with the observation of XRD patterns ( Fig.…”
Section: Preparation and Characterization Of Mo Carbidesmentioning
confidence: 99%
“…Similarly to most carbides, the structure can accommodate a large concentration of defects on the "interstitial" carbon positions, leading to substoichiometric TiC 1-x , with 0.535 < x < 0.023. The binary Mo-C system has several phases most of which have two compositions, MoC and Mo 2 C. The stoichiometric fcc-MoC phase, which crystallizes in a NaCl-type structure (B1-type) is metastable [16]. Important features such as the carbon nonstoichiometry and a possible ordered structure for the carbon vacancies still remain unexplained up to date.…”
Section: Introductionmentioning
confidence: 99%